A CYLINDER SEAL FROM TELL ABU AL-DHAHAB DATED TO THE FIRST SEALAND DYNASTY (1740–1374 BC). (December 2021) - Taher Al-Zubaidi, Ahmed K.; Attia, Mohammed S.
Abstract : This article presents a unique cylinder seal found at the site of Tell Abu al-Dhahab, in the Iraqi marshes. The cylinder seal, made of alabaster, is dated to the First Sealand Dynasty period and contains a scene with an introduction to a seated deity. It is accompanied by an inscription identifying the father of its owner as the overseer of the incantation priests. The aim of the article is both to discuss the cylinder seal, but also contextualize it within the temple where it was found and the period to which it is dated.